Effects of different types of exercises on pain, quality of life, depression, and body composition in women with fibromyalgia: A three-arm, parallel-group, randomized trial - Erkan Kolak; Füsun Ardıç; Gülin Fındıkoğlu (Archives of Rheumatology, 2022)
Objectives: This study aims to compare the efficacy of three different exercise types on pain, health-related quality of life (HRQoL), depression, and body composition in women with fibromyalgia (FM). Patients and methods: Between June 2019 and December 2019, a total of 41 women with FM (mean age: 46.7+9.4 years; range, 24 to 62 years) were randomly allocated into Group 1 (n=13, supervised aerobic plus stretching), Group 2 (n=13, supervised resistance plus stretching), and Group 3 (n=15, home-based stretching). All exercises were performed three times per week for 12 weeks and were individualized by measuring the maximal oxygen consumption (VO2max) for aerobic exercise and one-repetition maximum (1-RM) test for resistance exercise. The main measures were pain intensity assessed by the Visual Analog Scale (VAS), severity by the Fibromyalgia Impact Questionnaire (FIQ), symptoms of depression by the Beck Depression Inventory, HRQoL by the Short-Form Health Questionnaire (SF-36), and body composition by bioelectrical impedance analysis. Results: The mean VAS difference (95% confidence interval [CI]): -2.61 (-1.94, -3.29); -2.61 (-1.82, -3.42); -1.07 (-0.49, -1.64) for Group 1, Group 2, and Group 3, respectively (p<0.001); however, there was no significant difference between the combined exercise groups. The FIQ scores decreased significantly in all exercise groups after training (p<0.05). At 12 weeks, 21 (80.8%) patients from combined groups and six (40%) patients from the stretching alone group achieved a minimal clinically significant difference defined as a 14% change in baseline FIQ scores (p=0.008). Other outcome parameters did not differ significantly among the groups. Conclusion: Supervised aerobics/muscle strengthening combined with stretching exercises reduced pain, and FM severity more than a home stretching exercise alone.